Pengaruh Nursery Rhymes terhadap Kemampuan Kosakata Reseptif pada Anak Usia Prasekolah di TK Negeri Pembina Trenggalek - Rahmaningrum, Citya; Muryanti, Muryanti (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: Nursery Rhymes is a song that is specifically made for children, that range from simple but happy notes and consist of lyrics that have specific meaning. While some rhymes seem designed purely to amuse, others are didactic and educational. Educational experts believe that nursery rhymes can sharpen children’s language skills. Through nursery rhymes, children can learn and understand many new vocabulary. Objectives: This study aims to find out the effect of nursery rhymes on receptive vocabulary skills in preschool children at TK Negeri Pembina Trenggalek. Methods: This study is a quantitative study with cross-sectional design. The sampling technique used in this study was purposive sampling with 52 respondents. The instruments used in this study were a nursery rhymes usage questionnaire and a receptive vocabulary skills test (Receptive One-Word Picture Vocabulary Test). The statistical test used in this study was Kendall's Tau. Results: The result of Kendall's Tau test showed a ρ value of 0.001 (ρ < 0.05) and a correlation strength of 0.428. This means that there is an effect of nursery rhymes on receptive vocabulary skills, with moderate correlation strength and positive correlation direction. That is, the more often children use nursery rhymes, the higher receptive vocabulary skills they have. Conclusion: There is an effect of nursery rhymes on receptive vocabulary skills in preschool children at TK Negeri Pembina Trenggalek. Keyword: nursery rhymes, receptive vocabulary skills, preschool children